Evaluation Of Mechanical Properties On Vulcanized SMRCV-60 And ENR-25 Of Flexible-Rigid Body Vibration Isolator - Salim, Mohd Azli; Md. Saad, Adzni; Rosszainily, Intan Raihan Asni; Wasbari, Faizil; Masripan, Nor Azmmi; Mohd Yusof, Norbazlan; Mohammed Hussin, Ahmed Al-Mola (Universiti Malaysia Perlis, 2020)
This paper presents the evaluation of tensile test results on mechanical properties of local natural rubber called the standard Malaysian rubber constant viscosity-60 and the epoxidized natural rubber 25% with different carbon loadings for vibration isolators. The tensile test was carried out to determine the breaking point for both specimens. Based on the results, the lowest recorded tensile strength was identified in rubber compound containing 0 phr carbon, and the maximum tensile strength values were evaluated with higher phr carbon. The results also showed that the carbon reinforcement was proportion with the values of the tensile strength. The recorded Young’s Modulus and the values of the modulus depend on the values of carbon content in the rubber compound. By increasing the percentage of carbon, the modulus also increased. The pattern of the stress-elongation curve was also significantly changed by increasing the tensile strength. The deformation of the secondary bonding within rubber and fillers was also evaluated and the bonding became stronger by increasing the carbon. In conclusion, it is found that by increasing the carbon percentage in both types of rubber compound contributes to higher mechanical properties of the samples.